The impact of open distance learning during covid-19 pandemic on social interaction among university students / Noor'Aina Abdul Razak, Nor Hanim Abd Rahman and Rafizah Kechil - Abdul Razak, Noor'Aina; Abd Rahman, Nor Hanim; Kechil, Rafizah (Unit Penerbitan JSKM, 2021)
Since the emergence of Covid-19 at the end of 2019, open distance learning (ODL) has become a new norm with the university students. There are numerous issues and challenges which have arisen during the ODL period that have affected all levels of study. Thus, this preliminary research is carried out to look at the impact of ODL on social interaction among the 191 students who had answered the questionnaires. The results show that most students felt ODL had a negative impact on their social interactions throughout the remote learning experience.